Determination of Total Phenolic Contents and Antioxidant Activity of Six flowers and the Development of Skin Lotion from Peacock Flower Extract - Lateh, Likit; Muninnoppamas, Jeerawit; Charoenmitmongkol, Sarilla (YRU Journal of Science and Technology, 2023)
The pigments found in flowers are abundant in bioactive compounds, especially antioxidants, which are beneficial for the skin. Incorporating these bioactive floral extracts into cosmetics is an intriguing alternative for skin care products. This study examines the total phenolic compounds using the Folin-Ciocalteu method and antioxidant activity following DPPH radical scavenging ability of six varieties of flowering plants, namely Jasmine (Ixora coccinea L.), Wlower Fence (Caesalpinia pulcherrima L.), Paper Flower (Bougainvillea glabra), Torch Ginger (Etlingera elatior (Jack) R.M. Smith), Golden Trumpet (Allamanda cathartica) and Golden Shower (Cassia fistula L.)., to determine the viability of formulating a skin lotion with antioxidant flower extracts. The results showed that Wlower Fence flower had the highest total phenolic content (432.85 mg GAE/g extract) and the maximum DPPH scavenging activity (85.19%) at 50 mg/ml. The pH of the lotion formulated with Wlower extract was measured to be 6.40 during the characteristic evaluation. In accordance with Thai SMEs Standard for moisturizers containing herbal ingredients that are governed by the Ministry of Industry, the lotion was stable and did not separate into distinct layers (TISI. S 15-2021). In conclusion, possesses significant antioxidant capabilities that are ideal for development as a lotion product for skin care and raising the standard for production as a community product in the future.